Interaksi Perlakuan Dosis Dan Suhu Pirolisis Pembuatan Biochar Kayu Meranti (Shorea spp.) Mempengaruhi Kecepatan Tumbuh Sengon (Paraserianthes moluccana) - Bangun Adi Wijaya; Melya Riniarti; Hendra Prasetia; Wahyu Hidayat; Ainin Niswati; Udin Hasanudin; Irwan Sukri Banuwa (ULIN: Jurnal Hutan Tropis, 2021)
The growth rate of Paraserianthes moluccana is effected by the planting medium quality. Biochar is a soil-improving agent that could improve soil quality. This study aimed to determine the effect of biochar made from meranti wood (Shorea spp.) by pyrolysis temperature at 400°C and 600°C and dose at 0 ton/ha, 25 ton/ha and 50 ton/ha factors through the growth rate of P. moluccana. The P. moluccana was planted within 2x2 m in the field. The size of planting holes was 100 x 60 cm, the biochar was placed at a depth of 100 cm to 20 cm, then it was covered with soil so that the root did not interact directly to the biochar. This research used 6 months old P. moluccana seedling, and was planted in field demplot for 8 months. The research used the Split Plot experimental design with 5 treatments and 7 repetitions. Data analysis used Analysis of Variance (ANOVA) and Least Significance Different (LSD). The effect of biochar could be seen since the 4th month of plantation. The results showed that biochar with a dose of 25 ton/ha and pyrolysis temperature of 600°C had a very significant effect on the increment of height and significant on diameter steam increment of P. moluccana; increased the rate of stem height 22.6% and stem diameter 23.6% faster than the control. Further research related to the dynamics of P. moluccana growth with a longer time is needed because the physical properties of biochar change over time.